Match and Mismatch of Lesson Plan at the Tenth Grade of MTI Pasia - Monalisa Monalisa; Widya Syafitri; Merry Prima Dewi; Hilma Pami Putri (Journal of English Language Teaching, 2022)
The purpose of this research was to discover whether the lesson plan composed by the MTI Pasia English teacher match or even mismatch based on curriculum 2013. Since the limited time during covid-19 pandemic, the teacher had issues establishing the device used to assess and the appropriate rubric by way of the indicator, as well as the construction of the standard of competency and basic competency, and also in selecting effective methods to be appropriate with the indicators.Another problem since teacher did not use media or other learning tools in the class. So, it made the class monotonous and boring. No visualization could make students less enthusiastic in the learning process.This research used descriptive qualitative research. It was conducted at MTI Pasia. The instruments were observation sheet and documention.The result showed 3 (three) conditions were match (Identity of Lesson Plan, the objectives of study and method of study), 3 (three) of them were less match (Score competence, basic competence and Indicator of competence achievement and the material of study) and the rest three condition were mismatch (Media, tools, and sources of study, the steps of teaching or teaching activity and Assessments) related to teacher’s lesson plan component.